Dans le signe du son. Bruit, voix, corps et improvisation - Davide Sparti (Images Re-Vues)
Relying on Michel Foucault’s concept of genealogy, this paper offers two coupled thesis’ concerning improvisation in jazz.   The first is a historical diagnosis: once the notion of a musical «work» (written and through-composed) has become the aesthetic paradigm to evaluate music in general, the (oral) practice of improvisation has been marginalized.    The second thesis is that improvisation has been perceived as threatening because of the way it is connected to the «sounding bodies» of those who enact it.   Every language has an implicit phonetic code: some sounds are admitted (and admired), others are not.  In a culture that emphasizes the visual and the written, a sound which does not fit in a code (say as part of the chromatic segmentation), hence a sound deprived of a semantic function, becomes threatening.   This is shown by exploring the ontological differences between seeing and hearing, and by analyzing both the case of John Cage and of jazz.  Especially jazz shows the extent to which improvisation is connected to the capacity to exploit the textural discrepancies between notes and sounds that go beyond specific musical notes (i.e., discrete and re-identifiable sounds, endowed with a name): it is the growl, the whine, the hard-hitting, edgy, raspy, coarse, harsh, guttural, hissing, screeching, broken, liquid, raucous - call it the grain of sound - that lends sound its affecting presence.